The Effect of Training Methods and Arm Power on Freestyle Swimming Speed of Tirta Taruna Swimmers - Premana, Daluhana Dwi; Rahayu, Tandiyo; Rustiadi, Tri (Journal of Physical Education and Sports, 2019)
This study aims to find out and analyze the differences in the effect of interval and continuous training method on the 100 meter swimming speed of Tirta Taruna swimmers in Yogyakarta. This study used a random sampling technique. The data collection technique used tests and measurements. This type of study was experimental research through treatment or treatment. The subjects of the study were 20 Tirta Taruna Yogyakarta swimmers. The sample was taken using a random sampling technique from the population of all swimmers. The research instrument used Two Hand Medicine Ball Test and Swimming Speed Test. Based on the results of the data analysis from the Anova results it was obtained that Fvalue = 0.312 and Ftable = 5.95, it means that Fvalue > Ftable, therefore, it can be stated that there was a significant correlation or relationship between training methods and arm power with the results of the third hypothesis showing that significant results between factor A (interval and continuous training method) and B (arm power) on the 100 meter swimming speed . The results related to the hypothesis of the training method proved that there was an interaction between the type of interval and continuous training method with arm power in effect on the 100meter freestyle swimming speed.